Weblog search engine based on quality criteria - Azimzadeh, Fatemeh; Ramli, Abdul Rahman; Mohd Ali, Borhanuddin; Ibrahim, Hamidah (Engg Journals Publications, 2011)
Nowadays, increasing amount of human knowledge is placed in computerized repositories such as the World Wide Web. This gives rise to the problem of how to locate specific pieces of information in these often quite unstructured repositories. Search engines is the best solved. Some studied show that, almost half of the traffic to the blog server comes from search engines. The more outgoing and informal social nature of the blogosphere opens the opportunity for exploiting more socially-oriented features. The nature of blogs, which are usually characterized by their personal and informal nature, dynamically and constructed on the new relational links required new quality measurement for blog search engine. Link analysis algorithms that exploit the Web graph may not work well in the blogosphere in general. (Goncalves et al 2010) indicated that most of the popular blogs in the dataset (70%) have a PageRank value equal -1, being thus almost invisible to the search engine. We expected that incorporated the special blogs quality criteria would be more desirably retrieved by search engines.